1980
DOI: 10.1139/v80-450
|View full text |Cite
|
Sign up to set email alerts
|

Absolute rate constants for hydrocarbon autoxidation. 29. Rate constants for abstraction of primary aliphatic hydrogens from 2,2-dimethylbutane by the tert-butylperoxy radical

Abstract: Rate constants for abstraction of primary and secondary hydrogens from 2,2-dimethylbutane by the tert-butylperoxy radical at temperatures from 323 to 353 K have been determined from autoxidations and co-autoxidations in the presence of tert-butyl hydroperoxide. At 333 K the rate constant for abstraction of a secondary hydrogen is ~1.5 × 10−3 M−1 s−1 and the rate constants for abstraction of a primary hydrogen from the tert-butyl and methyl groups of 2,2-dimethylbutane are ~4 × 10−5 and ~6 × 10−5 M−5 s−1 respec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1983
1983
2015
2015

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…3 Rate constants of about 0.0015 M À1 s À1 obtained for the abstraction of secondary hydrogens by ROO clearly demonstrate that such reactions are slow. 4 Coote et al recently used high-level kinetic modelling techniques to demonstrate that in polymers without activated C-H bonds the subsequent reactions of ROOH (eqn (4) and (5) in Scheme 1) do not provide a sufficiently strong driving force to compensate for the endothermicity of the radical propagation Scheme 1 Polymer autoxidation mechanism proposed by Boland et al 1 through eqn (3). 5 It was concluded that only hydrogen abstractions by ROO , which lead to capto-datively or resonance stabilized radicals should be possible.…”
Section: Introductionmentioning
confidence: 99%
“…3 Rate constants of about 0.0015 M À1 s À1 obtained for the abstraction of secondary hydrogens by ROO clearly demonstrate that such reactions are slow. 4 Coote et al recently used high-level kinetic modelling techniques to demonstrate that in polymers without activated C-H bonds the subsequent reactions of ROOH (eqn (4) and (5) in Scheme 1) do not provide a sufficiently strong driving force to compensate for the endothermicity of the radical propagation Scheme 1 Polymer autoxidation mechanism proposed by Boland et al 1 through eqn (3). 5 It was concluded that only hydrogen abstractions by ROO , which lead to capto-datively or resonance stabilized radicals should be possible.…”
Section: Introductionmentioning
confidence: 99%